2019
DOI: 10.3390/f10050374
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of a Multiple-Branches Mutant Terminal Buds in Betula platyphylla × B. pendula

Abstract: To investigate the molecular mechanism of the mutation of a multiple-branches birch mutant (br), we explored genes that were genome-wide differentially expressed in the main and lateral branches’ apical buds of br. The plant architecture not only has effects on the process of plant growth and development, but also affects the agronomic characters. In woody plants, branches determine the application value of timber. Therefore, analyzing genes that were differentially expressed in br apical buds will bring new i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 79 publications
2
2
0
Order By: Relevance
“…The study results showed that the mutant plant was characterized by multiple branches, short branches, and short leaves, while the wild-type plant was characterized by few branches, long branches, and long leaves. Similar results were also reported in few other plants, such as physic nut (Chen et al, 2019) and birch (Han et al, 2019). In addition, the observational and statistical analyses of mutant grafted seedlings showed that the variant traits could be retained in grafted plants.…”
Section: Changes In Morphological and Cytological Structures Of Mutant Plantssupporting
confidence: 85%
See 1 more Smart Citation
“…The study results showed that the mutant plant was characterized by multiple branches, short branches, and short leaves, while the wild-type plant was characterized by few branches, long branches, and long leaves. Similar results were also reported in few other plants, such as physic nut (Chen et al, 2019) and birch (Han et al, 2019). In addition, the observational and statistical analyses of mutant grafted seedlings showed that the variant traits could be retained in grafted plants.…”
Section: Changes In Morphological and Cytological Structures Of Mutant Plantssupporting
confidence: 85%
“…Cell division, expansion, and differentiation affect the fundamental processes of plant organ growth and development and affect the plant phenotypes (Sugiyama, 2005;Yang et al, 2015). In addition, the shoot apical meristem (SAM) is essential for the development of plants and is responsible for the development of leaves, stems, and flowers (Han et al, 2019). Therefore, we analyzed 23 DEGs related to cell division, differentiation, and SAM activity to further study the differences between wild-type and mutant plants (Figure 5A).…”
Section: Degs Involved In Cell Division Cell Differentiation and Sam Activitymentioning
confidence: 99%
“…Compared with MP, OP developed more branches at an early stage and the leaf axillary buds produced spiny spur shoots. Similar results have been reported in other species, such as birch and larch ( Han et al., 2019 ; Cai et al., 2021 ). In addition, the vascular bundles and abaxial epidermal cells of MP leaves were larger than those of OP, and the areal proportion of the pith, xylem, and phloem in new shoots of MP from the base to the tip was greater than that of OP, and almost no conducting tissue had differentiated at the shoot tip of OP.…”
Section: Discussionsupporting
confidence: 91%
“…The meristem cells of buds undergo genetic changes during cell division, leading to the development of lateral branches ( Leng et al., 2021 ). The shoot apical meristem (SAM) is also crucial to plant development and is responsible for the development of leaves, stems, and flowers ( Han et al., 2019 ). The SAM gives rise to leaf primordia during the vegetative growth stage and an inflorescence meristem in the transitional stage from vegetative growth to reproductive growth.…”
Section: Introductionmentioning
confidence: 99%